Lightweight and Privacy-Preserving Data Aggregation for Mobile Multimedia Security - Sugang Ma; Tiantian Zhang; Axin Wu; Xiangmo Zhao (IEEE Access, 2019)
With the continuous development of multimedia technology, a growing number of multimedia applications have emerged. The demand for multimedia services continues to grow. But the development of multimedia services is still hampered by inherent security. Privacy and integrity of multimedia data are two key issues for implementing mobile multimedia security. At present, most data privacy-preserving solutions have a trusted third party, which may become the bottleneck of the system. And, the computational efficiency of the client is inefficient. In this paper, a lightweight and privacy-preserving data aggregation for mobile multimedia is proposed. In the proposed scheme, the terminal calculation is lightweight and there is no trusted third party in our scheme. Besides, multimedia big data and personal multimedia data are balanced by creating virtual aggregation areas and the system performance is improved by adopting batch verification in our scheme. Security analysis shows that the presented scheme can guarantee the privacy, confidentiality and integrity of the personal multimedia data. The performance analysis indicates the proposed scheme is lightweight.